Penyelesaian Sengketa Perceraian Melalui Mediasi dan Hubungannya Dengan Hadhanah (Hak Asuh Anak) di Pengadilan Agama Stabat (Studi Perkara No : 980/Pdt.G/2021/PA.stb) - Nabilla Karima (Peduli Riset dan Pengabdian Masyarakat, 2022)
Efforts to settle cases by taking proceedings in the Religious Courts must of course meet the feasibility of the case being brought to trial with various aspects that must be met. Likewise, household problems faced by Muslims can be submitted to the realm of law through the Religious Courts so that the parties get permanent legal certainty. In general, the problems that are often raised in religious courts are problems regarding divorce, namely the imposition of talak by the husband and the divorce lawsuit filed by the wife. The results of this study are that in the application of Hadhanah's decision, the judge is based on the best interests of the child as stated in the child protection law number 23 of 2002 and also the human rights law no. 39 of 1999. The judge also did not impose his will on the rule of article 105 letter a in the KHI which explains that the custody of children under the age of 12 is only with the mother, but can also be given to the father if a mother does not meet the eligibility requirements for child care. Â